Anion and sulfonamide inhibition studies of an α-carbonic anhydrase from the Antarctic hemoglobinless fish Chionodraco hamatus. Issue 23 (1st December 2015) - Cincinelli, Alessandra; Martellini, Tania; Vullo, Daniela; Supuran, Claudiu T.
Graphical abstract: Abstract: An α-carbonic anhydrase (CA, EC 4.2.1.1) has been purified from the Antarctic hemoglobinless fish Chionodraco hamatus (icefish). The new enzyme, denominated ChaCA, has a good catalytic activity for the physiologic CO2 hydration to bicarbonate reaction, similar to that of the low activity human isoform hCA I, with a k cat of 5.3 × 10 5 s −1, and a k cat /Km of 3.7 × 10 7 M −1 s −1 . The enzyme was inhibited in the submillimolar range by most inorganic anions (cyanate, thiocyanate, cyanide, bicarbonate, halides), whereas sulfamide, sulfamate, phenylboronic/phenylarsonic acids were micromolar inhibitors, with K I s in the range of 9–77 μM. Many clinically used drugs, such as acetazolamide, methazolamide, dorzolamide, brinzolamide, topiramate and benzolamide were low nanomolar inhibitors, with K I s in the range of 39.1–77.6 nM. As the physiology of CO2 /bicarbonate transport or the Root effect in this Antarctic fish are poorly understood at this moment, such inhibition data may give a more detailed insight in the role that CAs play in these phenomena, by the use of inhibitors described here as physiologic tools.